Ionien und Kleinasien in früher außerbiblischer Bezeugung - Görg, Manfred (Biblische Notizen, 2005)
During the current excavations in the area of the Funerary Temple of Amenhotep III. (Thebes-West) some new toponyms were found. One of them should be identified with Ionia, which would be the oldest testimony of the famous toponym in Minor Asia.. Furtheron the cilician cities Adana and Tarsus are possibly named. At least we are confronted with a preform for the well known Asia.